Joint responsibility in the development of effective wind-turbine collision-reducing solutions - May, Roel (Frontiers in Energy Research, 2023)
With the rapid acceleration of wind energy development there is a growing need to meet the consequences this has for the natural environment. Failing to mitigate environmental impacts is an important cause of conflict in wind energy projects, leading to costly delays in planned wind energy development. It is therefore of the utmost importance to identify effective solutions and measures to reduce such impacts. This requires that the joint responsibility for mitigation across stakeholders is recognized and acted upon. This is exemplified with the black-blade concept that has shown to reduce bird collision rates at the Smøla wind-power plant in Norway by 70%. While presented as a ‘golden bullet’ solution in the media, there remain unanswered challenges that need to be addressed. However, instead of disagreeing on the uncertain efficacy elsewhere, I pose that collaborative and transdisciplinary action is needed to jointly resolve remaining challenges and actively seek for solutions to support the sound implementation of promising wind-turbine collision-reducing solutions.